2008
DOI: 10.1152/ajpendo.00762.2007
|View full text |Cite
|
Sign up to set email alerts
|

Failure of adrenal corticosterone production in POMC-deficient mice results from lack of integrated effects of POMC peptides on multiple factors

Abstract: Karpac J, Czyzewska K, Kern A, Brush RS, Anderson RE, Hochgeschwender U. Failure of adrenal corticosterone production in POMC-deficient mice results from lack of integrated effects of POMC peptides on multiple factors. Am J Physiol Endocrinol Metab 295: E446 -E455, 2008. First published June 17, 2008 doi:10.1152/ajpendo.00762.2007.-Production of corticosteroids from the adrenal gland is a multistep process in which corticosterone is enzymatically processed from its precursor cholesterol. The main hormone reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This is contrary to our hypothesis that increased adrenal responsiveness in critical illness is associated with increased steroidogenic activity in the adrenal. However, these effects on adrenal gene expression observed in sustained critical illness are presumably the consequence of prolonged ACTH depletion observed in these patients, and are consistent with the adrenal alterations observed in mice lacking POMC, the gene that encodes for the precursor of ACTH (Karpac et al 2008). Taken together, these observations suggest that in acute critical illness associated with an inflammatory response, cytokines and other immunemodulators may be responsible for elevated plasma levels of CORT.…”
Section: Ultradian Rhythm Of Glucocorticoids In Human Disease and Crisupporting
confidence: 77%
“…This is contrary to our hypothesis that increased adrenal responsiveness in critical illness is associated with increased steroidogenic activity in the adrenal. However, these effects on adrenal gene expression observed in sustained critical illness are presumably the consequence of prolonged ACTH depletion observed in these patients, and are consistent with the adrenal alterations observed in mice lacking POMC, the gene that encodes for the precursor of ACTH (Karpac et al 2008). Taken together, these observations suggest that in acute critical illness associated with an inflammatory response, cytokines and other immunemodulators may be responsible for elevated plasma levels of CORT.…”
Section: Ultradian Rhythm Of Glucocorticoids In Human Disease and Crisupporting
confidence: 77%
“…Considering the extensive acute and chronic impact of ACTH on the adrenal cortex, persistently low plasma ACTH concentrations could thus also profoundly affect the adrenal cortex. Indeed, lack of ACTH, as occurs in pro-opiomelanocortin (POMC) knock-out mice, causes atrophic and hypofunctional adrenal glands (Coll et al, 2004;Karpac et al, 2008), and POMC-deficiency in human patients is characterized by loss of adrenocortical zonational structure, adrenocortical lipid depletion, reduced ACTH signaling and adrenal atrophy/ failure (Krude and Gruters, 2000).…”
Section: Consequences Of Reduced Cortisol Breakdown During Critical Imentioning
confidence: 99%
“…Unfortunately, given the nature of the study, blood samples were not available to correlate the observed changes with plasma ACTH and cortisol concentrations. However, these results are strikingly reminiscent of the phenotype of pro-opiomelanocortin-deficient mice, which suggests that a sustained lack of ACTH-effect on the adrenal cortex may indeed explain these findings (44). These changes in the adrenal cortex of prolonged ICU stay-patients also help to explain the reported 20-fold higher incidence of symptomatic adrenal insufficiency in critically ill patients being treated in the ICU for more than 14 days (45).…”
Section: E Boonen and G Van Den Berghementioning
confidence: 92%